From the Agroecology Initiative to the Multifunctional Landscapes Program: A Partner Forum - Staiger, Simone; Carvajal, Andrea (2024)
Summary of a Forum with implementing partners of the Agroecology Initiative online to reflect on three years of collaborative research.